Strategi Selebgram Dalam Membangun Personal Branding Melalui Pengelolaan Akun Instagram - Tiara Mita (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
Selebgram is currently widely used as a promotional media carried out by a brand because it is considered effective in promoting a product that is packaged in its own way so that it looks more natural. Celebrity is also considered as a tool in building the image of a brand or service. Personal branding is the process of how individuals are seen as a brand by their target market, personal branding is aimed at attracting more clients who actively shape public perceptions. In determining the strategy to be carried out, the researcher uses the concept of personal branding according to Peter Montoya. In addition, this study also uses the theory of communication privacy management to see how celebrities manage their personal information on their Instagram account. This study uses a descriptive qualitative research approach. The data collection technique in this study was to conduct direct field observations, namely to conduct direct interviews with research informants to obtain data about the personal branding of celebrities in managing personal information on their Instagram accounts. The results of the study show that celebrities in building personal branding have their own privileges according to the content they choose. Celebrities in managing privacy information in general already know the limits of their privacy information with the public on social media, so they understand what information can and cannot be shared on their social media. They have good management, between themselves and netizens.